1998
DOI: 10.1088/0031-9155/43/10/004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods of therapy level calibration at60Co gamma beams

Abstract: The accuracy and traceability of the calibration of radiotherapy dosimeters is of great concern to those involved in the delivery of radiotherapy. It has been proposed that calibration should be carried out directly in terms of absorbed dose to water, instead of using the conventional and widely applied quantity of air kerma. In this study, the faithfulness in disseminating standards of both air kerma and absorbed dose to water were evaluated, through comparison of both types of calibration for three types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous direct or indirect comparisons at the BIPM (cf Boutillon et al 1994, Boutillon andAndreo 1997) had shown differences of up to 1% between some laboratories, even for those of a given geographical region where a common dosimetry protocol is used. The differences between chamber calibrations provided by some laboratories, reported by Bjerke et al (1998), may be of relevance in the present context only for the few k Q values measured by clinical users (Vatnitsky et al 1995, Palm 2000. Many experimental k Q values have been obtained using Fricke dosimetry.…”
Section: Experimental Data Of High-energy Photon K Q Factorsmentioning
confidence: 86%
“…Previous direct or indirect comparisons at the BIPM (cf Boutillon et al 1994, Boutillon andAndreo 1997) had shown differences of up to 1% between some laboratories, even for those of a given geographical region where a common dosimetry protocol is used. The differences between chamber calibrations provided by some laboratories, reported by Bjerke et al (1998), may be of relevance in the present context only for the few k Q values measured by clinical users (Vatnitsky et al 1995, Palm 2000. Many experimental k Q values have been obtained using Fricke dosimetry.…”
Section: Experimental Data Of High-energy Photon K Q Factorsmentioning
confidence: 86%
“…Although the air kerma calibration network is intrinsically more sensitive to systematic errors (see for example Bielajew and Rogers 1992) as in all standard dosimetry laboratories it is determined using graphite walled ionization chambers, it has not yet been proven that an absorbed dose calibration network can reach the same level of consistency as the air kerma calibration network. A recent experimental study by Bjerke et al (1998) showed that direct calibration in terms of absorbed dose to water using calculated k Q values could reduce the total uncertainty on absorbed dose determination in the user beam by 1-1.5%. However, they found that, depending on the standard laboratory, discrepancies of up to 1.5% could show up due to the change from air kerma based dosimetry to absorbed dose based dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Results show that the N D,ar values for the parallel plate chambers determined in 60 Co beams are 1.2% higher than the value obtained in high energy electron beams. This difference in measurements series may be related, like in some published studies (12,13,17) , but this hypothesis is promptly discarded, since, in the charge measurement, the maximum uncertainty between measurements is ±0.15% for each voltage. So, this discrepancy is assigned to parallel plate chambers walls attenuation correction factors supplied by the protocol, which should not be coherent when calibration in photon beams is performed.…”
Section: Discussionmentioning
confidence: 93%